Complete Inhibition of Endotoxin-Induced Coagulation Activation in Chimpanzees with a Monoclonal Fab Fragment against Factor VII/VIIa - Biemond, Bart J; Levi, Marcel; ten Cate, Hugo; Soule, Howard R; Morris, Lori D; Foster, David L; Bogowitz, Cheryl A; van der Poll, Tam; Büller, Harry R; ten cate, Jan Wouter (Thrombosis and Haemostasis, 1995)
Gram-negative sepsis is oftentimes complicated by activation of coagulation with disseminated intravascular coagulation and microthrombosis. This may contribute to the associated morbidity, multiple organ failure and death. Recent studies have established that the tissue factor-dependent pathway of blood coagulation has a significant participatory role in the initial endotoxin-induced activation of coagulation. Tissue factor (TF), expressed on the surface of activated monocytes and endothelial cells forms cell surface complexes with free circulating factors VII and VIIa. The latter complex proteolytically activates factors X and IX. Recent in vivo experiments have shown that a rapidly neutralizing TF monoclonal antibody prevents and arrests the endotoxin- induced activation of coagulation and similar studies have shown to reduce mortality in baboons. In this study we describe the preparation of a factor VII/VIIa neutralizing monoclonal Fab fragment and characterize its effect on in vivo activation of coagulation during experimental endotoxemia in chimpanzees.Four chimpanzees received a bolus intravenous injection of 4 ng/kg endotoxin in combination with Fab fragments of a factor VII/VIIa neutralizing murine monoclonal antibody (12D10) at a dose of either 50 μg/kg (n = 2) or 100 μfig/kg (n = 2). Four control animals received a bolus injection of endotoxin alone. Administration of the 12D10 Fab fragments, immediately preceding the endotoxin bolus injection, effectively blocked the endotoxin-induced activation of coagulation. Plasma levels of products of in vivo activation, namely F1+2, TAT complexes and FpA remained at baseline values. The administration of 12D10 resulted in a rapid decline in factor VII/VIIa antigen levels which remained below 5 ng/ml for 180-240 min, followed by a rapid return to baseline levels. Endotoxin administration resulted in activation of the fibrinolytic system as reflected by a rapid increase in plasma plasmin- α2-antiplasmin complexes. Administration of 12D10 was without effect on the endotoxin-induced fibrinolytic activation.In conclusion, this study confirmed the importance of the TF: VII complex in the initial, endotoxin-induced activation of coagulation which was completely blocked by neutralizing all free and tissue factor-complexed factor VII/VIIa by a specific monoclonal Fab fragment. Activation of fibrinolysis was not influenced. Therefore, neutralization of factor VII/VIIa might be a promising therapeutic option in preventing endotoxin-induced microthrombosis during Gram-negative sepsis.